WHAT ARE MIDDLE‐SCHOOL GIRLS LOOKING FOR IN PHYSICAL EDUCATION? - Gibbons, Sandra; Humbert, Louise (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
Many young women become disillusioned with physical education in their high‐ school years. Mounting evidence suggests that this disillusionment starts in early adolescence. This article discusses the experiences of female students in co‐ educational, middle‐school, physical education classes. Focus group interviews, individual interviews, and questionnaires were used to collect data. The following themes emerged: personal competence, a moving body is a healthy body, choice and variety for a lifetime, and an emerging sense of gender equity. Results provide guid‐ ance for the development of physical education curricula to gain and hold the interest of female, middle‐school students. Key words: adolescence, female, curriculum, exercise Bien des jeunes filles sont désillusionnées quant aux cours d’éducation physique au secondaire. Il y a de plus en plus d’indications que cette désillusion commence au début de l’adolescence. Les auteures présentent les expériences de filles dans les cours d’éducation physique mixtes au secondaire. Les données furent colligées au moyen d’entrevues de groupe, d’entrevues individuelles et de questionnaires. Les thèmes suivants ont surgi : la compétence personnelle, un corps en mouvement est un corps sain, choix et variété tout au long de la vie, émergence d’un sentiment d’égalité entre les sexes. Les résultats permettent d’orienter l’élaboration de programmes d’éducation physique qui sauront capter et maintenir l’intérêt des filles au secondaire. Mots clés : adolescence, filles, programme d’études, exercice physique